Regularity for Almost Convex Viscosity Solutions of the Sigma-2 Equation (Journal of Mathematical Study, 2021)
We establish interior regularity for almost convex viscosity solutions of thesigma-2 equation.
Keywords: Regularity; viscosity solution; fully nonlinear; elliptic partial differential equation.